A Clinical Experience with Patients of Syphilis - Ahmed, Syed Afaq; Sheikh, Riaz A; Khan, Ikram–ullah (International Journal of Pathology, 2018)
Twenty five consecutive cases of Syphilis presenting to the dermatology department of Pakistan Institute of MedicalSciences, Islamabad, were reviewed regarding the clinical pattern of presentation, laboratory findings and their response totreatment. Other associated sexually transmitted diseases were also looked for and HIV status was also determined. Most ofthe patients responded well to penicillin and those not responding were adequately treated with erythromycin. Patients’ ageranged from 10 to 70 years; most of the patients were clustered between 20 to 40 years. There were 22 males and 3 femalepatients. Following clinical signs were seen in the patients: Body Rash with particular involvement of the face, palms, solesand genitalia, oral and other mucous membrane lesions, hair loss, lymphadenopathy and condylomata lata.